Interfacial Fe5C2-Cu catalysts toward low-pressure syngas conversion to long-chain alcohols - Yinwen Li (Nature Portfolio, 2020)
Long-chain alcohols synthesis from syngas conversion is a promising route for the production of high-value chemicals. Here the authors show that a heterogeneous Fe5C2/Cu catalyst derived from layered double hydroxides precursor exhibits excellent performance with a space time yield of 0.101 g gcat −1 h−1 at a low pressure of 1 MPa.